2004
DOI: 10.1002/hyp.5650
|View full text |Cite
|
Sign up to set email alerts
|

Pressure variations in peat as a result of gas bubble dynamics

Abstract: Transient high pore-water pressures, up to 50 cm higher than ambient pressure, developed over the summer season at various depths in a shallow (1 m) fen peat. The excess pressures had a pattern of gradual increases and sharp drops, and their initiation and release typically corresponded to abrupt changes in atmospheric pressure. We conclude that these phenomena depend on gas bubbles (probably methane) generated by biological activity, both by clogging pores and by building up pressure as they grow. These trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 17 publications
2
66
1
Order By: Relevance
“…Bellisario et al, 1999;Treat et al, 2007). The association between lower WT position and higher CH 4 efflux could result from higher substrate temperatures, as in this study, or because the lower WT position reduces pressure, thereby allowing gas bubbles to be released (Kellner et al, 2004;Strack et al, 2005).…”
Section: Varying Controls On Ch 4 Fluxesmentioning
confidence: 63%
“…Bellisario et al, 1999;Treat et al, 2007). The association between lower WT position and higher CH 4 efflux could result from higher substrate temperatures, as in this study, or because the lower WT position reduces pressure, thereby allowing gas bubbles to be released (Kellner et al, 2004;Strack et al, 2005).…”
Section: Varying Controls On Ch 4 Fluxesmentioning
confidence: 63%
“…If the biomass increases, then emission through bubbles may decrease. As the plant biomass was low, the clogging of bubbles in porous peat materials may explain the observation, as the fibrous nature of peat restrains bubbling (Kellner et al 2004). This result suggests that the sensitivity to atmospheric pressure variations may be higher in open water sites than in vegetated sites.…”
Section: Resultsmentioning
confidence: 99%
“…However the approximately double the rate of biogas evolution and colour change produced for specimen B are consistent with its partially submerged condition. Although Wardwell et al (1983) reported complete conversion of organic substrate into gases is not considered to be responsible for the increase in compressibility of organic deposits, the presence of gases has nevertheless been proven to affect the compressibility of peat since the dynamics of gas bubbles in peat deposits significantly affects hydrological conditions and hydraulic properties (Kellner et al, 2004. For instance, hydraulic conductivity reduces in value with an increase in volume of entrapped gas bubbles (Beckwith and Baird, 2001;.…”
Section: Effect Of Decomposition Process On Compressibility Of Peatmentioning
confidence: 99%
“…Since rates of primary consolidation and creep settlements are governed by drainage and sequential expulsion of water from macro-and micropores (Berry, 1983;Huat et al, 2011), reductions in hydraulic conductivity significantly reduce the settlement rate, exacerbating the long-term settlement problem. Although an abundance of gas bubbles (mainly methane) can be found at depth in peat deposits under anaerobic condition (Kellner et al, 2004), potential effects arising from reductions in hydraulic conductivity due to entrapped gases are currently largely ignored in considering peat compressibility.…”
Section: Effect Of Decomposition Process On Compressibility Of Peatmentioning
confidence: 99%